A Comparison of Puncture and Continuous Pump Analgesia With Two Different Approaches to Thoracic Paravertebral Block for Thoracic Surgery - Huang, Qiao-wen; Lu, Zhi-wei; Li, Jia-bin; Zhang, Wen-qing; Jiang, Li-wei; Lin, Zhi-jian (Frontiers in Surgery, 2022)
BACKGROUND: This study aims to compare the success rate of thoracic paravertebral block (TPVB) and the effect of postoperative analgesia between two approaches. METHODS: A total of 34 patients with American Society of Anesthesiology (ASA) physical status score II–III, undergoing an optional thoracoscopic surgery, were randomly assigned to a parasagittal approach group (group P, n=17) and a transverse intercostal approach group (group T, n=17). The catheterization time, success rate of the puncture and catheterization, block plane and effect at the surgical site were compared between two groups. The mean arterial pressure and heart rate were recorded, as well as the cold tactile block plane and numeric rating scale (NRS) at 0.5, 2, 4, 8, 12, 24, and 48 h after surgery. RESULTS: The catheterization time in group P was significantly longer than that in group T (P<0.05). The success rate of catheterization in group P was lower than that in group T , but no statistical significance (P=0.085). There was no significant difference in the success rate of punctureor and blocking effect of the surgical site at 30 minutes postinjection between two groups (P>0.05). There was no significant difference in the cold tactile block plane and NRS scores between two groups at 0.5, 2, 4, 8, 12, 24, and 48 h postoperatively (P>0.05). CONCLUSION: This study suggests that there is no significant difference in postoperative block level or pain score for thoracoscopic surgery between ultrasound-guided parassagittal and transverse intercostal approach , but the parassagittal approach takes longer and has a higher failure rate.